If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7x+12=2x-3
We move all terms to the left:
7x+12-(2x-3)=0
We get rid of parentheses
7x-2x+3+12=0
We add all the numbers together, and all the variables
5x+15=0
We move all terms containing x to the left, all other terms to the right
5x=-15
x=-15/5
x=-3
| 2(6+y)-5y=21 | | 7(x-3)=15+5 | | d22=60 | | 2(6+y)–5y=21 | | (2x+15)+61=180 | | 4y+2=6y-20 | | 9w-8+2(2w+2)=-2(w+7) | | 2x+1=3x+13 | | 4.50.25a+0.5=4.5 | | 2x+1=3×+13 | | -21=s-17 | | -2r=-r+11 | | 6(y+3)+3=9 | | 10(x−1)=5(x+2) | | 8h-12=6h | | 3x+9=8x+14 | | t-10/4=-4 | | 17+w=19 | | t–104=-4 | | -5a+10a=10 | | -4=2(s+5) | | 1=-6z+5z | | 5(x+3)–3x=55 | | 69=-391+4x | | 18=7r+18 | | 2(y-6)+3=2y-7 | | 15x=69.6 | | 7n^2+10=-19n | | 18+7r=18 | | -2x+1=3x-4 | | 4x-3-3(2x)=12+3x | | (2x+15)+6=180 |